2022
DOI: 10.1021/acs.joc.1c02237
|View full text |Cite
|
Sign up to set email alerts
|

Pyrido[1,2-e]purine: Design and Synthesis of Appropriate Inhibitory Candidates against the Main Protease of COVID-19

Abstract: A series of tricyclic and polycyclic pyrido[1,2- e ]purine derivatives were designed and synthesized via a two-step, one-pot reaction of 2,4-dichloro-5-amino-6-methylpyrimidine with pyridine under reflux conditions. Various derivatives of pyrido[1,2- e ]purine were also synthesized by substituting the chlorine atom with secondary amines. After careful physiochemical and pharmacokinetic predictions, the inhibitory effects of the synthesized compounds against the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…As derivatives of [1,2,4]triazolo [4,3-a]pyrimidine incorporating selenium has not been synthesized and studied, it is anticipated that these compounds are good candidates for biological activities. Therefore, in continuation of our previous studies, selenopheno [2,3-e] [1,2,4] triazolo [1,5-c]pyrimidine derivatives [40], [1,3]selenazolo [5,4-e][1,2,4]triazolo [1,5-c]pyrimidine [41,42], and pyrido[1,2-e]purine [43], herein, we report the synthesis of organoselenides with metal-free procedure comprising of the alkylation of selenium anions.…”
Section: Introductionsupporting
confidence: 72%
“…As derivatives of [1,2,4]triazolo [4,3-a]pyrimidine incorporating selenium has not been synthesized and studied, it is anticipated that these compounds are good candidates for biological activities. Therefore, in continuation of our previous studies, selenopheno [2,3-e] [1,2,4] triazolo [1,5-c]pyrimidine derivatives [40], [1,3]selenazolo [5,4-e][1,2,4]triazolo [1,5-c]pyrimidine [41,42], and pyrido[1,2-e]purine [43], herein, we report the synthesis of organoselenides with metal-free procedure comprising of the alkylation of selenium anions.…”
Section: Introductionsupporting
confidence: 72%
“…Very recently, Moghimi et al reported the synthesis of pyrido[1,2-e]purine derivatives (195) via a two-step, one-pot reaction of 2,4-dichloro-5-amino-6-methylpyrimidine (194) with 2-amino pyridine (168 a) under reflux conditions. [136] In this approach, 2,4-dichloro-5-amino-6-methylpyrimidine reacted with 2-amino pyridine; which acts as both a solvent and a substrate under the reflux conditions afforded 2-chloro-4methylpyrido[1,2-e]purine (195) in 44 % yield. Various derivatives of pyrido[1,2-e]purine (196) were then synthesized by substituting the chlorine atom with a variety secondary amines (Scheme 58).…”
Section: Synthesis Of Pyrido[12-e]purinesmentioning
confidence: 99%
“…Treatment of the amides with NaOH yielded the corresponding 1,3-dialkyl-7H-xanthine analogues 137) and evaluated in vitro for adenosine receptor binding affinity and in vivo for bronchospasmolytic effects. [121] The condensation reaction of 1,3-dimethyl-5,6diaminouracil (121) with para-substituted phenyl acetic acids (135) in the presence of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDCI) in MeOH, followed by the cyclization with NaOH provided the xanthine derivatives (136) which on nucleophilic substitution of Cl atom with various heterocyclic amines gave the desired xanthine derivatives 137 (Scheme 42).…”
Section: Synthesis Of Xanthines From 56-diaminouracil and Carboxylic ...mentioning
confidence: 99%
“…30 Among the triazole derivatives, we became interested in 3-alkyl-pyrido [1,2-e] [1,2,4]triazolo [4,3-a]purines, due to their roles as potential candidates against the main protease of COVID-19. 31 Thus, a deep understanding of their structures can be useful to design novel inhibitors. Shiri and coworkers reported the synthesis of 3-alkyl-pyrido [1,2-e] [1,2,4]triazolo [4,3-a]purines (3-H, 3-Me and 3-Et) by 2-chloro-4-methylpyrido[1,2-e]purine (1) via a nucleophilic aromatic substitution (S N Ar) amination mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Shiri and coworkers reported the synthesis of 3-alkyl-pyrido [1,2-e] [1,2,4]triazolo [4,3-a]purines (3-H, 3-Me and 3-Et) by 2-chloro-4-methylpyrido[1,2-e]purine (1) via a nucleophilic aromatic substitution (S N Ar) amination mechanism. 31 The treatment of (1) with hydrazine hydrate led to 2-hydrazinyl-4-methylpyrido[1,2-e]purine (2), and after that, the reaction between (2) and three triethyl orthoesters (RC(OEt) 3 )s was promoted to give three derivatives of heterocyclic compounds (3) as two regioisomers of 3-H, 3-Me and 3-Et substituents (Scheme 1). They reported that the ring-closing in the presence of triethyl orthoesters goes through a regioselective cyclization reaction.…”
Section: Introductionmentioning
confidence: 99%